Export Restrictions of Indonesian Nickel Ore Based on the Perspective of Quantitative Restriction Principles in General Agreement on Tariffs and Trade - Doan Mauli Tua Siahaan; Ibrahim Sagio; Evi Purwanti (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2021)
This study aims to determine whether Indonesia’s nickel ore export restriction policy is in accordance with the principles of international economic law. It is because Indonesia’s actions in implementing quantitative restrictions on the export of nickel ore are deemed to have violated one of the principles in the General Agreement on Tariffs and Trade, namely the principle of prohibiting quantitative restrictions. This principle is contained in Article XI: 1 GATT. Data was collected through library research techniques. Namely by collecting and analyzing writings and literatures that are closely related to the problems that are being researched by the author, and analyzing data with descriptive analytical techniques, so that Indonesia can analyze their export restriction policies with juridical provisions in international trade law. The results shows that Indonesia’s action is in accordance with Article XI: 2 (a), which regulates the exception to Article XI: 1, with certain conditions which is a dispensation from the principle of quantitative restriction. Indonesia’s nickel ore export restrictions were also implemented to protect the environment in order to prevent scarcity and to encourage the battery industry in Indonesia to improve the economy. So that Indonesian policy is valid and can be justified by international law.